2005
DOI: 10.1105/tpc.105.033415
|View full text |Cite
|
Sign up to set email alerts
|

The TomatoAux/IAATranscription FactorIAA9Is Involved in Fruit Development and Leaf Morphogenesis

Abstract: Auxin/indole-3-acetic acid (Aux/IAA) proteins are transcriptional regulators that mediate many aspects of plant responses to auxin. While functions of most Aux/IAAs have been defined mainly by gain-of-function mutant alleles in Arabidopsis thaliana, phenotypes associated with loss-of-function mutations have been scarce and subtle. We report here that the downregulation of IAA9, a tomato (Solanum lycopersicum) gene from a distinct subfamily of Aux/IAA genes, results in a pleiotropic phenotype, consistent with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
511
2
33

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 523 publications
(575 citation statements)
references
References 55 publications
29
511
2
33
Order By: Relevance
“…Yet, the prevailing idea is that fruit growth and metabolism are predominantly supported by photoassimilate supply from the source (Ruan et al, 2012), and in this regard, our data cannot rule out that the higher sugar content observed in the transgenic lines could also arise from a more efficient import of photoassimilate into fruit. Indeed, altering auxin sensitivity via down-regulation of tomato IAA9 has been reported to promote the development of vascular bundles (Wang et al, 2005), which may enhance sink strength and sugar supply to the fruit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, the prevailing idea is that fruit growth and metabolism are predominantly supported by photoassimilate supply from the source (Ruan et al, 2012), and in this regard, our data cannot rule out that the higher sugar content observed in the transgenic lines could also arise from a more efficient import of photoassimilate into fruit. Indeed, altering auxin sensitivity via down-regulation of tomato IAA9 has been reported to promote the development of vascular bundles (Wang et al, 2005), which may enhance sink strength and sugar supply to the fruit.…”
Section: Discussionmentioning
confidence: 99%
“…These two fragments were then cloned into the pGA643 binary vector in the antisense orientation under the transcriptional control of the Cauliflower mosaic virus 35S (35SCaMV) promoter and the nopaline synthase terminator. All transgenic plants were generated by Agrobacterium tumefaciens-mediated transformation according to Wang et al (2005). All experiments were carried out using homozygous lines from F3 or later generations.…”
Section: Plant Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it was shown that expression of a GA 20-oxidase gene was induced by pollination in tomato (Rebers et al 1999;Serrani et al 2007), and the importance of SlDELLA, which represses GA signaling and tomato fruit set, has also been demonstrated (Marti et al 2007). In additional, IAA9 and ARF8, both transcriptional regulators of the auxin response, were shown to be part of an important signal for fruit set (Wang et al 2005;Goetz et al 2007). However, many other genes remain to be discovered and investigated.…”
mentioning
confidence: 99%